Farrow-to-Finish Swine Cost-Return Budget - Dhuyvetter, Kevin C.; Tokach, Mike D. (My University, 2001)
This publication examines the cost and returns for farrow to finish swine production in Kansas.
MF292_2001_10
Keywords: MF292; Livestock; Economics; MF